Defaunation of large mammals leads to an increase in seed predation in the Atlantic forests - Galetti, Mauro [UNESP] (2015)
Defaunation can trigger cascading events in natural communities and may have strong consequences for plant recruitment in tropical forests. Several species of large seed predators, such as deer and peccaries, are facing dramatic population collapse in tropical forests yet we do not have information about the consequences of these extinctions for seed predation. Using remote camera traps we tested if defaunated forests have a lower seed predation rate of a keystone palm (. Euterpe edulis) than pristine areas. Contrary to our expectation, we found that seed predation rates were 2.5 higher in defaunated forests and small rodents were responsible for most of the seeds eaten. Our results found that defaunation leads to changes in the seed predator communities with potential consequences for plant-animal interactions.